PENCAIRAN DANA DEPOSITO OLEH AHLI WARIS WARGA NEGARA ASING TANPA SURAT WASIAT, STUDI KASUS PADA PUTUSAN PENGADILAN NEGERI DENPASAR NOMOR 1103/PDT.G/ PN DPS MENGENAI PENENTUAN AHLI WARIS - Lapriasih, Iluh Dwi; Lestari, Anak Agung Adi (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Deposits are a type of savings that can only be withdrawn at a specified time based on an agreement between the customer and the bank. In one of the BPR banks, for foreign national customers (WNA), there are requirements for the withdrawal of time deposits that must be met in accordance with the bank's regulations. One of them is the submission of a certificate of heirs certified by a notary from the customer's home country, which is then translated by a certified translation agency. Alternatively, WNA customers can use a will made with the customer's lawyer and certified by a notary in their home country. It is noted that the law in the customer's home country, such as in England, does not recognize documents such as a certificate of heirs or a will. The research method used by the author is normative legal research. The types of approaches used are statutory and conceptual approaches with data collection techniques using library studies, where after the legal materials are collected, analysis will be carried out using qualitative methods.